2013
DOI: 10.1007/s12031-013-0018-4
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Expression of the Arf6 Guanine-Nucleotide Exchange Factor Cytohesin-1 in Mice Exhibits Enhanced Myelin Thickness in Nerves

Abstract: The myelin sheath consists of a unique multiple layer structure that acts as an insulator between neuronal axons to enhance the propagation of the action potential. In neuropathies such as demyelinating or dismyelinating diseases, chronic demyelination and defective remyelination occur repeatedly, leading to more severe neuropathy. As yet, little is known about the possibility of drug target-specific medicine for such diseases. In the developing peripheral nervous system (PNS), myelin sheaths form as Schwann c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Fyn directly binds, phosphorylates, and activates cytohesin-1. Fyn results in promoting myelination, especially the initiating events ( Yamauchi et al ., 2012 ; Torii et al ., 2013 ). It is conceivable that Fyn, acting downstream of Tyro3, may activate Arf6 to promote myelination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fyn directly binds, phosphorylates, and activates cytohesin-1. Fyn results in promoting myelination, especially the initiating events ( Yamauchi et al ., 2012 ; Torii et al ., 2013 ). It is conceivable that Fyn, acting downstream of Tyro3, may activate Arf6 to promote myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently the tissues were postfixed with 4% paraformaldehyde, which was then replaced by 20% sucrose, and the tissues were embedded in Tissue-Tek reagent (Sakura Finetechnical, Tokyo, Japan). Microtome sections on glass slides were blocked using Blocking One reagent; subsequently they were incubated with primary antibodies and then with fluorescence-labeled secondary antibodies ( Yamauchi et al ., 2012 ; Torii et al ., 2013 ). Glass slides were mounted using Vectashield reagent.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that cytohesin-1 is a GEF for Arf6 to promote myelination by Schwann cells (Yamauchi et al ., 2012; Miyamoto et al ., 2013a; Torii et al ., 2013). In this study, we find that cytohesin-2 is involved in oligodendrocyte differentiation and myelination, although it is possible that GEFs other than cytohesin family members activate Arf6.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the regulators known as guanine nucleotide exchange factors (GEFs, positive regulators) and GTPase-activating proteins (GAPs, negative regulators) participate in oscillating between active GTP-bound states and inactive GDP-bound ones. It is currently unknown whether Arf signals are involved in oligodendrocyte morphological differentiation during the myelination process, although, in the peripheral nervous system (PNS), Arf6-GEF cytohesin-1 (Kolanus et al ., 1996; Meacci et al ., 1997) and the downstream activation of Arf6 are required for morphological changes in Schwann cells, the myelin-forming glial cells in the PNS, during the myelination process (Yamauchi et al ., 2012; Miyamoto et al ., 2013a; Torii et al ., 2013). …”
Section: Introductionmentioning
confidence: 99%
“…47 Consistent with these reports, in vivo expression of the cytohesin-1 in Schwann cells of mice increases the thickness of the sciatic nerve myelin. 48 These reports strongly suggest the possibility that Arf6 in Schwann cells also play an important role in the developmental process of myelination during development of the PNS.…”
Section: Please Scroll Down For Articlementioning
confidence: 93%